The Self-Reflection in Hunger of Memory Critical Theory Psychoanalysis - Seddeeqah Hadi Salhb Al-Quraishi (Periodica Journal, 2023)
This thesis is about the self-reflection in Hunger of Memory according the critical theory. Critical Theory has a narrow and a broad meaning in philosophy and in the history of the social sciences .Critical Theory in the narrow sense designates several generations of German philosophers and social theorists in the western European Marxist tradition known as the Frankfurt school .A according to these theorists ,a critical theory may be distinguished from a traditional theory according to a specific practical purpose :a theory is critical to the extent that it seeks human emancipation from slavery ,acts as a liberating…..influence and works to create a world which satisfies the need and powers of human beings
Keywords: self-reflection; Critical Theory; Hunger of memory